INNOVATIVE EDUCATION MANAGEMENT FOR ISLAMIC RELIGIOUS LEARNING: INTEGRATION OF 21ST CENTURY COMPETENCIES - Sa'idi (Managere: Indonesian Journal of Educational Management, 2023)
This research aims to explore the implementation of 21st-century competency principles in Islamic learning at MTs Muhammadiyah 5 Al Fajar Kapas Bojonegoro, with a particular focus on improving students' critical thinking skills through the use of HOTS questions, giving rewards, and peer tutoring methods. The background to this research is based on the urgent need to reform the education system to suit global demands and prepare students to face future challenges. The research method used is descriptive qualitative, with a field study approach involving observation, interviews, and documentation to collect relevant data. The research results showed that applying HOTS questions, rewards, and peer tutoring significantly improved students' critical thinking skills. This method also contributes to forming students' character, including increasing their sense of responsibility, empathy, and the ability to communicate and collaborate. In conclusion, integrating 21st-century competencies in Islamic learning enriches students' academic understanding and improves their character.